Magnetic nanoparticles hyperthermia in a non-adiabatic and radiating process - C. A. M. Iglesias (Nature Portfolio, 2021)
Abstract We investigate the magnetic nanoparticles hyperthermia in a non-adiabatic and radiating process through the calorimetric method. Specifically, we propose a theoretical approach to magnetic hyperthermia from a thermodynamic point of view. To test the robustness of the approach, we perform hyperthermia experiments and analyse the thermal behavior of magnetite and magnesium ferrite magnetic nanoparticles dispersed in water submitted to an alternating magnetic field. From our findings, besides estimating the specific loss power value from a non-adiabatic and radiating process, thus enhancing the accuracy in the determination of this quantity, we provide physical meaning to a parameter found in literature that still remained not fully understood, the effective thermal conductance, and bring to light how it can be obtained from experiment. In addition, we show our approach brings a correction to the estimated experimental results for specific loss power and effective thermal conductance, thus demonstrating the importance of the heat loss rate due to the thermal radiation in magnetic hyperthermia.